Nurturing Children's Faith in the Modern Era with the Philosophy of Si Tou Timou Tumou Tou - Vera E Burhan (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
In this work, the Minahasan philosophy 'Si Tou Timou Tumou Tou,':] Man lives to humanize others is an initial building block in exploring children's faith development in Modern society. Tomohon was chosen as the research setting to investigate the factors that foster spirituality in children through parental pastoral care and community involvement. The method employed in the study is non-experimental since the participants' responses in the students' interviews and observations are used to explain the challenges and opportunities in cultivating the children's faith. In the study, the darkness tries to harm children through technology and peer pressure, but this Si Tou Timou Tumou Tou philosophy signifies how parents can help children's spirits. ST 1 The findings, therefore, support the Minahasan philosophy of involving the parents to spend time with the child and the family by worshipping, eating together, and having family fun. Last and most significantly, the community, particularly the church, for this particular study is also revealed by effectively supporting parental spiritual care by offering the proper framework suitable for children's faith development. Given the facts elicited in this research study, intervention strategies for children's faith development could call for the use of traditional practices, parents, and community as a way of helping in the faith development of children. This work contributes to the existing body of knowledge by understanding how Indigenous philosophies can be applied within spiritual education and how the Community interface affects children's spirituality in the contemporary world.